(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In current study for the first time, we were able to successfully synthesize single-crystalline ZTO nanorods using a straightforward microwave irradiation technique. ZTO nanorods have a length of up to several micrometers and a diameter of 25-50 nm and are single-crystalline, structure obtained from XRD. UV-VIS diffuse reflectance spectroscopy was used to examine the optical properties. The photoluminescence spectrum (PL) of the nanorods at room temperature shows stable broad blue-green emissions around the 400–600 nm wavelength range, with a maximum center at 490 nm and 520 nm. This is in good agreement with the reported values of 3.25 eV. ZTO nanorods have potential applications in high-performance supercapacitors, according to these findings. faradaic method of reaction